CHINESE FAIRYTALE “WEAVER GIRL AND COWHERD”: A SOURCE OF LEARNING CHINESE LANGUAGE AND CULTURE. - Raj, Arpana (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Fairytales never get old and outdated. Even in the 21st century of a globalised and digitalised world, it remains a source of inspiration for our basic human nature, inspiration, and imagination. Besides this, fairytales are also a strong source for understanding a particular culture, its customs, traditions, and common practices. China is no exception. Even in today’s information age the essence and importance of ancient fairytales have not got mild. Since learning the Chinese language and culture has become one of the new global trends at rise; this paper will explore the link between ancient Chinese fairytales and Chinese language learning. Taking a case study of the famous fairytale “Weaver girl and the Cowherd” from the Chinese language textbook “Elementary Chinese Reader” referred in India, the paper tries to explore how the tale helps foreign learners to understand the language, culture, geographical set-up, social norms as well as the aspirations of Chinese people at a particular time. And further, it highlights the relevance of fairy tales in the present information age world.